REPORTS OF MORPHOLOGY Official Journal of the Scientific Society of Anatomists, Histologists, Embryologists and Topographic Anatomists of Ukraine © 2022 National Pirogov Memorial Medical University, Vinnytsya journal homepage: https://morphology-journal.com 57 DOI: 10.31393/morphology-journal-2022-28(2)-08 Reports of Morphology, Vol. 28, No 2, Pages 57-61 ISSN 1818-1295 eISSN 2616-6194 Pelvic circumference in young men and young women studying in higher education institutions of Bukovina, depending on the sport - Karatieieva, Svitlana; Slobodian, Oleksandr; Музика, Наталія; Hauriak, Olena; Chorna, N.M. (Official Journal of the Scientific Society of Anatomists, Histologists, Embryologists and Topographic Anatomists of Ukraine, 2022)
In recent decades, anthropological research methods have been widely used by scientists to correctly predict the achievement of high sports results. The aim of the study is to find out the features of the pelvic circumference of young men (YM) and young women (YW), who study in higher education institutions in Bukovina, depending on the sport. Anthropometric parameters were studied for 115 first and second year students of higher education institutions in Chernivtsi, aged 16 to 21, including 78 (67.82 %) YM and 37 (32.18 %) YW, the main group - 75 (65.22 %), were students of I- II courses of the Faculty of Physical Culture and Human Health of Yuriy Fedkovych Chernivtsi National University, control group - 40 (34.78 %) - college students and students of the Faculty of Dentistry of Bukovina State Medical University. Among the students of the main group - 57 (76.00 %) YM and 18 (24.00 %) YW. Students of the main group, in addition to physical activity, which was included in the program of their specialty, additionally engaged in the following sports: football - 40 (53.34 %), of which YM - 36 (48.00 %), YW 4 (5.34 %), volleyball - 18 (24.00 %), of which YM - 9 (12.00 %),YW 9 (12.00 %), tennis - 10 (13.34 %), of which YM - 8 (10.67 %), YW 2 (2.67 %), basketball - 7 (9.32 %), of which YM - 4 (5.32 %), YW 3 (4.00 %), the control group consisted of 21 (52.50 %) YM and 19 (47.50 %) YW, which are loaded with hours of physical education, according to the curriculum of their specialty and additionally All students were determined to determine body weight and pelvic circumference according to the method of Bunak V. V. in the modification of Shaparenko P. P. Statistical analysis of the data was performed using a licensed program RStudio. Analyzing the average pelvic circumference of YM and YW, it is noteworthy that the average pelvic circumference among both study groups is much larger in YM compared to YW (representatives of the main group - respectively 83.40±3.01 cm and 78.31±3.01 cm; representatives of the control group - respectively 88.47±3.01 cm and 75.31±3.01 cm). In the main group, depending on the sport, volleyball players (YM - 86.11±3.02 cm; YW - 77.55±3.03 cm) and basketball players (YM - 85.50±3.03 cm; YW - 76.66±3.03 cm) have the largest pelvic circumference, followed by football players (YM - 81.52±3.02 cm, YW - 75.00±3.02 cm), and the smallest tennis players - 81.00±3.02 cm YM and 74.50±3.02 cm YW. Based on the regression analysis, it was found that weight is a significant factor for pelvic circumference.
Keywords: athletes, anthropometry, pelvic circumference, sex differences.